2012
DOI: 10.1542/peds.2012-0568
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Chromosomal Microarray Analysis

Abstract: The disorders diagnosed by chromosomal microarray analysis frequently have clinical features that need medical attention, and physicians respond to the diagnoses with specific clinical actions, thus arguing that microarray testing provides clinical utility for a significant number of patients tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 104 publications
0
53
0
4
Order By: Relevance
“…It has also been reported that microarray analysis in support of a patient's standard of care impacts patient management up to 70% of the time. [7][8][9][10] Because clinical management decisions are sometimes subjective, the percentages vary. In two large retrospective studies representing slightly less than a total of 75,000 patients, it was estimated that 35-46% of patients with pathogenic cytogenetic findings and 7% of all patients would have some sort of change in clinical management based on microarray results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that microarray analysis in support of a patient's standard of care impacts patient management up to 70% of the time. [7][8][9][10] Because clinical management decisions are sometimes subjective, the percentages vary. In two large retrospective studies representing slightly less than a total of 75,000 patients, it was estimated that 35-46% of patients with pathogenic cytogenetic findings and 7% of all patients would have some sort of change in clinical management based on microarray results.…”
Section: Introductionmentioning
confidence: 99%
“…In two large retrospective studies representing slightly less than a total of 75,000 patients, it was estimated that 35-46% of patients with pathogenic cytogenetic findings and 7% of all patients would have some sort of change in clinical management based on microarray results. 7,8 Two other studies reported on retrospective cohorts for which actual rates of clinical implications were available and found that more than 50% of all patients with abnormalities had clinical management changes based on microarray results. 9,11 Although microarrays are now common first-tier tests in this patient population and Original research article supported by medical guidelines from the American College of Medical Genetics and Genomics (ACMG), 12 the International Collaboration for Clinical Genomics (ISCA/ICCG), 5 and the American Academy of Neurology, 13 payer reimbursement for testing is inconsistent, indicating the need for additional systematic studies assessing the changes in patient management that occur as a result of microarray testing.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous reports on the diagnostic utility of CMA 4,5,15 and its wide acceptance by the clinical genetics community, some health insurance companies do not provide reimbursement for this test, particularly for patients with isolated or nonsyndromic DD/ID and ASDs. The Secretary's Advisory Committee on Genetics, Health, and Society concluded that "coverage and reimbursement are critical to ensuring appropriate access to genetic tests and services and their integration into clinical practice. "…”
mentioning
confidence: 99%
“…11,13, 42 Studies have estimated that at least 5 to 7% of individuals undergoing CMA testing, or approximately a third of those with a pathogenic finding, receive a result with specific implications for medical management. [33][34][35] Reviews of medical records demonstrate that clinicians are basing medical management decisions on outcomes of CMA, [36][37][38] thus supporting the clinical utility of the test. It is possible that these implications for medical management may be due to what is considered an "incidental" finding, or a finding that is unrelated to the reason for testing.…”
Section: Clinical Use Of Chromosomal Microarray Testingmentioning
confidence: 96%
“…It will also discuss the clinical use of CMA testing, where its diagnostic utility has made it a recommended first-tier test for many individuals presenting for genetic or neurologic evaluation. 11,14,31,32 Its increased clinical use has yielded evidence for clinical utility, [33][34][35][36][37][38] although some payers and specialists feel formal evidence is still lacking. [39][40][41] …”
Section: Introductionmentioning
confidence: 99%